Screening, brief intervention and referral to treatment (SBIRT): implementation barriers, facilitators and model migration. (February 2017) - Vendetti, Janice; Gmyrek, Amanda; Damon, Donna; Singh, Manu; McRee, Bonnie; Del Boca, Frances; Del Boca, Frances K.; Babor, Thomas F.; Bray, Jeremy W.
Abstract: Aims: To identify barriers and facilitators associated with initial implementation of a US alcohol and other substance use Screening, Brief Intervention, and Referral to Treatment (SBIRT) grant program, and to identify modifications in program design that addressed implementation challenges. Design: A mixed‐method approach used quantitative and qualitative data, including SBIRT provider ratings of implementation barriers and facilitators, staff interview responses and program documentation. Setting: Multiple sites within the first seven programs funded in a national demonstration program in the United States. Participants: One hundred and two SBIRT providers were surveyed; 221 SBIRT stakeholders and staff were interviewed. Measurements: Mean ratings of barriers and facilitators were calculated using provider survey responses. An inductive content analysis of interview responses identified factors perceived to support and challenge implementation; program modifications that occurred over time were recorded. Findings: Providers rated pre‐selected implementation facilitators higher than barriers. Content analysis of interview responses revealed six themes: committed leaders; intra‐ and inter‐organizational communication/collaboration; provider buy‐in and model acceptance; contextual factors; quality assurance; and grant requirements. Over time, programs tended to: adopt more efficient 'pre‐screen' item sets; screen for risk factors in addition to alcohol/substance use; use contracted specialists to deliver SBIRT services; conduct services in high‐volume emergency department and trauma center settings; and implement on‐site and telephonic treatment delivery. Conclusions: Screening, Brief Intervention and Referral to Treatment program implementation in the United States is facilitated by committed leadership and the use of substance use specialists, rather than medical generalists, to deliver services. Many implementation challenges can be addressed by an adequate start‐up phase focused on comprehensive education and training, and on the development of intra‐ and inter‐organizational communication and collaboration; opinion leader support; and practitioner and host site buy‐in.